The Natural History of Canadian Mammals. - Naughton, Donna (University of Toronto Press, 2012)
Comprehensive and immensely valuable, The Natural History of Canadian Mammals will become a treasured companion for scientific researchers, animal lovers, and all those wishing to gain a greater appreciation of Canada's natural wonders.